Pengaruh Ukuran Perusahaan dan Rotasi Auditor Terhadap Kualitas Audit - Nikita Dwi Harla; Elen Haditiya Baharudin; Rafiq Naufal Rahman; Ida Rosnidah; Firman Hidayat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aimed to ascertain the effect of firm size and auditor rotation on the audit quality of technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. This research employed a sample of 10 organizations observed across five periods, meeting the requirements for sample selection. This yields 50 data points. The study utilized purposive sampling, and logistic regression analysis the analytical instrument to examine the hypothesis. This study's findings indicated that the firm's size and the auditors' rotation did not affect the quality of auditors. This implies that the competence of an auditor was not determined by external variables, such as the firm's size or the rotation of auditors.